Impact of co-infections and immune responses on clinical severity of human adenovirus 3 and 7 infections in hospitalized children with lower respiratory tract infections: a comparative study - Xiaolin Ma; Yuting Wu; Ri De; Hailan Yao; Feng He; Yi Wang; Wei Wang; Chao Yan; Qinwei Song; Chunjie Guo; Li Wen; Linqing Zhao; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundThe pathogenic distribution of co-infections and immunological status of patients infected with human adenovirus serotypes 3 or 7 (HAdV-3 or HAdV-7) were poorly understood.MethodsThis study involved a retrospective analysis of respiratory specimens collected from enrolled children with lower respiratory tract infections (LRTIs), positive for HAdV-3 or HAdV-7 from January 2017 to December 2019. Demographic data, clinical features, laboratory and radiographic findings were compared to delineate the impact of co-infections, and immune responses on clinical severity of HAdV-3 or HAdV-7 infections.ResultsAmong 1311cases enrolled, there were 66 infected with HAdV-3 and 58 with HAdV-7. HAdV-7-infected patients exhibited more prolonged fever (100% vs 89.4%, p=0.014), pneumonia (100% vs 89.4%, p=0.014), hypoxia (34.5% vs 12.1%, p=0.003), higher propensity for aspartate aminotransferase exceeding 80U/L (21.1% vs 4.7%, p=0.006), D-Dimer exceeding 1.65mg/L (64.9% vs 12.5%, p<0.001), consolidation (50.0% vs 27.4%, p=0.011), and pleural effusion (32.8% vs 6.5%, p<0.001), co-infections with Mycoplasma pneumoniae (77.1% vs 32.6%, p<0.001), and multiple infections (56.8% vs 41.3%, p=0.007), compared to those with HAdV-3 infections. Immune cell analysis indicated that HAdV-7 infections led to a more pronounced decrease in CD3+ T cells (1596.8 vs 2444.8 cells/𝛍l, p=0.042), CD8+ cytotoxic T cells (668.6 vs 774.0 cells/µl, p=0.045), and increased NK cell percentages (11.5% vs 9.0%, p=0.044) compared to HAdV-3 infections.ConclusionsHospitalized children with HAdV-7-associated LRTIs exhibit greater severity, multiple infections, and significant potential for greater cellular immune dysregulation compared to those with HAdV-3 infection, indicating a more severe clinical course and distinct pathogenic profiles.